2016
DOI: 10.3892/or.2016.4999
|View full text |Cite|
|
Sign up to set email alerts
|

miR-124 inhibits proliferation and invasion of human retinoblastoma cells by targeting STAT3

Abstract: A growing body of evidence suggests that microRNA-124 (miR-124) functions as tumor-suppressor, and involves in tumor initiation, development and metastasis in major classes of human cancers; however, the biological role and underlying molecular mechanism of miR-124 in retinoblastoma (RB) remain unknown. Therefore, we investigated the biological activity and underlying molecular mechanism of miR-124 in human retinoblastoma. In the present study, our results demonstrated the downregulation of miR-124 in RB tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 33 publications
(39 reference statements)
3
25
0
Order By: Relevance
“…Recently, a study showed that STAT3 expression was upregulated in RB tissues, and that knockdown of STAT3 inhibited cell proliferation in vitro, and suppressed tumor growth in vivo (28,29). A recently study revealed that STAT3 was regulated by miR-124 in RB (18). In this study, we found that miR-29a overexpression significantly inhibited STAT3 expression and expression of its downstream genes cyclin D1, Bcl-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 48%
“…Recently, a study showed that STAT3 expression was upregulated in RB tissues, and that knockdown of STAT3 inhibited cell proliferation in vitro, and suppressed tumor growth in vivo (28,29). A recently study revealed that STAT3 was regulated by miR-124 in RB (18). In this study, we found that miR-29a overexpression significantly inhibited STAT3 expression and expression of its downstream genes cyclin D1, Bcl-2 and MMP-9.…”
Section: Discussionsupporting
confidence: 48%
“…Numerous miRNAs contribute to RB initiation and progression by regulating cell proliferation, cell cycle distribution, apoptosis, migration, invasion and metastasis (31)(32)(33). Therefore, further investigation on the expression, roles and associated mechanisms of RB-related miRNAs may be beneficial to develop novel strategies for patients with this malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, miRNAs have been widely demonstrated to serve essential functions in the initiation and progression of RB via regulating the expression of specific genes (23). For instance, Liu et al (24) reported that the proliferation, migration and invasion of human RB cells were significantly suppressed by miR-124 in a signal transducer and activator of transcription 3-dependent manner. Lei et al (25) reported that miR-101 was downregulated in RB tissues and suppressed tumor cell growth and proliferation by inhibiting the expression of enhancer of (26) demonstrated that miR-34a was downregulated in RB tissues and enhanced tumor cell chemosensitivity and promoted cell death by targeting high mobility group box 1 to suppress autophagy.…”
Section: Discussionmentioning
confidence: 99%